Effect of Posthatch Feed Restriction on Broiler Breast Muscle Development and Muscle Transcriptional Regulatory Factor Gene and Heparan Sulfate Proteoglycan Expression - Velleman, S.G.; Nestor, K.E.; Coy, C.S.; Harford, I.; Anthony, N.B. (International Journal of Poultry Science, 2010)
The effect of an immediate posthatch growth restriction mediated through a 20% growth restriction the first 2 wk posthatch was studied for its effect on pectoralis major muscle morphological structure and the expression of the myogenic transcriptional regulatory factors, MyoD and myogenin, and the heparan sulfate proteoglycans syndecan-4 and glypican-1. Broiler chicks at hatch were divided into a full fed (control) group or a treatment group with feed managed to maintain a body weight 80% of control weight through 2 wk posthatch. At the end of 2 wk, the growth restricted chicks were put on full feed diet without further restriction. By 1 d posthatch, the morphological structure of the pectoralis major muscle in the growth restricted birds was not well organized into muscle fiber bundles with distinct individual muscle fibers as observed in the control group. The difference in the morphological structure remained throughout the 42 d of the study. The growth restricted birds had increased fiber necrosis and larger and more extensive fat cell depots beginning at 28 d posthatch. The BW of the growth restricted birds was significantly reduced compared to control birds through 28 d. Pectoralis major weight was significantly reduced through 28 d. The expression of genes required for the proliferation and differentiation of muscle cells was affected by the growth restriction. MyoD and syndecan-4 are both genes expressed during proliferation and both of these genes had elevated expression during the first wk of the growth restriction whereas the differentiation genes, myogenin and glypican-1, were significantly reduced in their expression during this period of time. Together these results suggest that the immediate posthatch feeding regimen to chicks is critical for the appropriate morphological development of the pectoralis major muscle, the formation of intramuscular fat depots, and the expression of genes necessary for muscle cell proliferation and differentiation.